2016
DOI: 10.18433/j31021
|View full text |Cite
|
Sign up to set email alerts
|

Nanotoxicity of Inert Materials: The Case of Gold, Silver and Iron

Abstract: -Nanotechnology has opened a new horizon of research in various fields including applied physics, chemistry, electronics, optics, robotics, biotechnology and medicine. In the biomedical field, nanomaterials have shown remarkable potential as theranostic agents. Materials which are considered inert are often used in nanomedicine owning to their nontoxic profile. At nanoscale, these inert materials have shown unique properties that differ from bulk and dissolved counterparts. In the case of metals, this unique b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 162 publications
0
33
1
Order By: Relevance
“…27 Second, nanoparticles production should be homogenous for better performance in vitro and in vivo. 28 On the other hand, zeta potential is important with respect to colloidal stability of the SLNs. Nanoparticles with a zeta potential between 20 and 40 mV will have sufficient repulsion to remain homogeneously dispersed in the aqueous dispersion.…”
Section: Preparation and Characterization Of Slnsmentioning
confidence: 99%
“…27 Second, nanoparticles production should be homogenous for better performance in vitro and in vivo. 28 On the other hand, zeta potential is important with respect to colloidal stability of the SLNs. Nanoparticles with a zeta potential between 20 and 40 mV will have sufficient repulsion to remain homogeneously dispersed in the aqueous dispersion.…”
Section: Preparation and Characterization Of Slnsmentioning
confidence: 99%
“…Lack of toxicity has been broadly documented for negatively charged GNPs (probably due to their bare surface) in the size range reported in this paper and at a dose of 1 mg/kg. 27 Thus, it could be assumed that lecithin-coated PGNPs and SGNPs could be safely used in vivo as preferred contrast agents.…”
Section: Results and Discussion Shape And Surface Morphology Of Npsmentioning
confidence: 99%
“…However, application of these gold nanostructures has been limited by the complex manufacturing procedure, high cost, and toxicity due to surface ligands. 27 In this paper, we report a novel route for one-pot synthesis of solid gold nanoparticles (SGNPs) and PGNPs as CT contrast agents. Both SGNPs and PGNPs were prepared and stabilized with lecithin.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles are usually used in food packaging, drinks, toothpaste, cars, and lubricants [13]. Umair M, et al (2016) considered that nanoparticles of gold are observed as biologically inert [14]. Nanoparticles (NPs) have specific properties which make them suitable for imaging, therapy, and drug delivery [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) have specific properties which make them suitable for imaging, therapy, and drug delivery [15]. According to the above mentioned report [14] and since gold nanoparticle of AuNP has shown anti-oxidant activity, this trail was designed to assess the antioxidant effect of AuNP on the liver toxicity induced by carbon -tetrachloride (CCl 4 ) in male rats.…”
Section: Introductionmentioning
confidence: 99%